Wound healing process – case report - Waszczyk-Łączak, Maja; Izdebska, Justyna; Ambroziak, Anna M. (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
The article presents the case of a 35-year-old patient with corneal thinning within the post-inflammatory scar. The Anterior Segment Optical Coherence Tomography showed a minimum thickness of the cornea of 92.0 μm. The patient was considered preliminarily eligible for penetrating corneal transplant surgery having considered a high risk of such procedure. She was started on 800.0 mg acyclovir five times daily and 8.0 mg methyloprednisolone once daily. Local improvement was achieved and the Anterior Segment Optical Coherence Tomography done 3 months later confirmed that corneal thickness increased to 396.0–399.0 μm. Methylprednisolone therapy was continued at a dose of 8.0 mg a day for six months, then at the reduced dose of 4.0 mg per day for the next three months to be eventually discontinued afterwards. Acyclovir therapy was continued for the next 12 months following the first month dose reduction to 400.0 mg administered four times daily.